Working women in transition to motherhood in Italy - Bertolini, Sonia; Musumeci, Rosy; Naldini, Manuela; Torrioni, Paola Maria (Journal of Romance Studies, 2015)
This article deals with the changing relationship between work and motherhood during the first pregnancy among a group of twenty-one highly educated women living in Turin (Northern Italy), who were interviewed during the months before childbirth with their male partners, in 2010-2012. It aims to illustrate the tensions between the dominant ideas and ideals of motherhood (the 'intensive mothering' model) and the pressing demands of the changing labour market. The data shows that ideas, plans and decisions concerning childcare arrangements are highly gendered, being influenced by the expectations of partners, employers and colleagues and by a work culture which is not family friendly. Within this Italian social and political context, a mother-to-be faces a dilemma which is perceived as a private issue that concerns only herself. The new transition to parenthood forces women to redefine their identity and career in a highly gendered manner. © Institute of Modern Languages Research 2015.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; charge mentale; conciliation famille-travail; europe; famille; italie; maternité; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques; travail

Anna, salle d'attente - Cornu, Emmanuelle (Écarts, 2015)
Anna a vingt-sept ans et n’a pas rencontré le grand amour. Elle saute quelques étapes dans son existence de jeune lesbienne et décide d’entrer dans la course à la maternité. Michaëlle, une globetrotteuse volage, vient bouleverser ses plans. C’est le coup de foudre. Anna tombe de haut et se voit confrontée à une décision douloureuse : nourrir son affection pour Michaëlle ou poursuivre son rêve parental. Dans le doute, Anna préfère une troisième option : elle abandonne les inséminations, opte pour l’adoption, puis s’acharne à transformer son amante en épouse fidèle. Les rêves d’Anna volent en éclats. De crise en crise, Anna tente de sortir de son marasme, mais s’enfonce dans la dépression. Anna troque une salle d’attente pour une autre.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; hétérosexisme; maternité; périodes historiques; québec; régions géographiques; santé; systèmes d'oppressions; thématiques